2013
DOI: 10.1097/ta.0b013e31827891b7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of packed red blood cell–to–fresh frozen plasma transfusion ratio of 4

Abstract: Therapeutic, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…We collected data for age, sex, mechanism of injury, injury severity score (ISS), abbreviated injury scale (AIS), time to arrival in ED, vital signs on arrival (heart rate, blood pressure, temperature), Glasgow Coma Scale (GCS), initial laboratory values (hemoglobin [Hb], hematocrit [Hct], PLT count, prothrombin time, activated partial thromboplastin time), international normalized ratio (INR), base deficit, pH, BIG score (base deficit + [2.5 × INR] + [15 – GCS]), length of hospital stay, length of pediatric intensive care unit stay, number of days on vasopressors, number of ventilator days, need for damage control surgery, patient death, cause of death, composite morbidity (included multiorgan failure, sepsis, acute respiratory distress syndrome, transfusion‐related acute lung injury [TRALI], abdominal compartment syndrome, and thrombotic complications), Glasgow Outcome Scale, intravenous fluid (IVF) use, and timing and amount of blood products given. Blood product volumes were recorded in milliliters when possible and converted to units using predefined definitions: 1 unit of plasma = 200mL, 1 unit of RBCs = 300mL, and 1 unit of PLTs = 50mL of apheresis PLTs . Plasma and PLT deficits were calculated assuming a balanced transfusion ratio of 1:1:1 units of plasma:PLTs:RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…We collected data for age, sex, mechanism of injury, injury severity score (ISS), abbreviated injury scale (AIS), time to arrival in ED, vital signs on arrival (heart rate, blood pressure, temperature), Glasgow Coma Scale (GCS), initial laboratory values (hemoglobin [Hb], hematocrit [Hct], PLT count, prothrombin time, activated partial thromboplastin time), international normalized ratio (INR), base deficit, pH, BIG score (base deficit + [2.5 × INR] + [15 – GCS]), length of hospital stay, length of pediatric intensive care unit stay, number of days on vasopressors, number of ventilator days, need for damage control surgery, patient death, cause of death, composite morbidity (included multiorgan failure, sepsis, acute respiratory distress syndrome, transfusion‐related acute lung injury [TRALI], abdominal compartment syndrome, and thrombotic complications), Glasgow Outcome Scale, intravenous fluid (IVF) use, and timing and amount of blood products given. Blood product volumes were recorded in milliliters when possible and converted to units using predefined definitions: 1 unit of plasma = 200mL, 1 unit of RBCs = 300mL, and 1 unit of PLTs = 50mL of apheresis PLTs . Plasma and PLT deficits were calculated assuming a balanced transfusion ratio of 1:1:1 units of plasma:PLTs:RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…One retrospective study by Nosanov indicated that there was not an association between higher plasma : RBC ratios and survival in a cohort of children transfused greater than 50% of their blood volume (Nosanov et al , ). A second prospective pilot study in children with burn injuries compared a 1 : 1 to 1 : 4 plasma : RBC ratio strategies, with more plasma and less RBCs administered in the 1 : 1 group, but no difference in PT/PTT, INR, haemoglobin or platelets between groups (Palmieri et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a paucity of evidence supporting DCR in children, it is being generalised to paediatric practice within MTPs for both traumatic and non-traumatic aetiologies (Nylund et al, 2009;Dressler et al, 2010;Chidester et al, 2012;Agrawal et al, 2013;Nosanov et al, 2013;Palmieri et al, 2013). Therefore, it is essential that DCR be studied specifically in children.…”
mentioning
confidence: 99%
“…The underlying assumption, supported by the limited intraoperative burn data reviewed above, is that bleeding results in coagulopathy during burn surgery. While the study by Palmieri et al did not demonstrate a difference in INR or PT/aPTT, equal component ratio transfusion did decreased overall pRBC use (47). This approach assumes that transfusing equal ratio blood products to restore whole blood functionality will minimize blood loss.…”
Section: Focused Reviewmentioning
confidence: 93%
“…Others suggest that equal ratio transfusion is not necessary during burn or soft tissue excision. While this position is not supported by definitive data, one small prospective randomized trial (n=8 per group) comparing a 1:1 versus 1:4 FFP to RBC ratio failed to find a difference in INR or PT/PTT (47). Additionally, data from the Hébert, et al study in 1999 (48) comparing restrictive versus liberal transfusion has been frequently generalized to the burn population, and was recently supported by an observational study in burned children with historical controls (45) and a retrospective review (44).…”
Section: Focused Reviewmentioning
confidence: 99%